Composite graphite material as well as preparation method and application thereof

By setting NaF-LiF composite particles on the surface of the graphite material to form a uniform SEI film, the problem of limited diffusion of lithium ions is solved, and the magnification and cycling performance of the graphite material are significantly improved.

CN119419264APending Publication Date: 2025-02-11SICHUAN ZICHEN TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538656.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The diffusion of lithium ions during the fast charging process of existing graphite negative electrode materials is limited, resulting in poor rate performance and cycling performance. The increased specific surface area of ​​the porous structure is not conducive to processing performance, and the transmission of lithium ions on the graphite surface is affected.

Method used

A composite graphite material is used, which includes a graphite core and NaF-LiF composite particles arranged on the surface, and a uniform and thin SEI film is formed by heat treatment, which improves the transmission rate of lithium ions and the protection of the electrode interface.

Benefits of technology

It significantly improves the rate performance and cycling performance of graphite materials, reduces the irreversible loss of lithium ions, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419264A_ABST
    Figure CN119419264A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite graphite material and a preparation method and application thereof. The composite graphite material comprises a plurality of composite particles, and each composite particle comprises a graphite inner core and a plurality of NaF-LiF particles arranged on the graphite inner core. According to the composite graphite material disclosed by the invention, the plurality of LiF-NaF composite particles are arranged on the surface of the graphite core, so that the lithium ion transmission rate can be increased, and the rate capability and the cycle performance of graphite can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite graphite material and a preparation method and application thereof. Background Art

[0002] Graphite is the most widely used negative electrode material in lithium-ion batteries. Its capacity is close to the theoretical specific capacity. With the demand for fast charging, the fast charging performance of graphite negative electrodes faces new challenges. The diffusion of lithium ions includes escaping from the positive electrode, diffusing in the electrolyte, passing through the diaphragm, passing through the SEI film on the graphite surface, and diffusing inside the graphite. Among them, the rate at which lithium ions pass through the SEI has an important influence on the fast charging performance of the graphite negative electrode.

[0003] Many people have conducted research on the diffusion of lithium ions in the negative electrode of lithium-ion batteries. Some have made porous graphite by etching graphite to increase the lithium ion transmission channels and thus improve the diffusion rate of lithium ions; others have coated the main inorganic salt components of SEI such as lithium carbonate and lithium fluoride on the graphite surface.

[0004] The applicant of the present invention has found that although the porous structure can improve the rate performance of graphite, in practical applications, the pore structure may increase the specific surface area of ​​graphite, which is not conducive to its processing performance. Moreover, a larger specific surface area will consume more lithium ions to form SEI film during the first charge and discharge, resulting in irreversible loss of lithium. The particles of lithium carbonate, lithium fluoride, etc. coated on the graphite surface are relatively large, which will affect the transmission of lithium ions on the graphite surface.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] An object of the present invention is to provide a composite graphite material which can effectively improve the cycle performance and rate performance of graphite.

[0007] Another object of the present invention is to provide a method for preparing the composite graphite material, which is simple and easy to implement, and the obtained composite graphite material has high capacity, high initial efficiency, good cycle performance and rate performance.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] A composite graphite material comprises a plurality of composite particles, wherein the composite particles comprise a graphite core and a plurality of NaF-LiF particles arranged on the graphite core.

[0010] In some embodiments, the NaF-LiF particles have a particle size of 10 to 100 nm.

[0011] In some embodiments, the mass content of element Li in the composite graphite material is 25 to 180 ppm, and the mass content of element sodium is 65 to 110 ppm.

[0012] In some embodiments, in the composite graphite material, the number of NaF-LiF particles with a particle size of 20 to 80 nm accounts for more than 80%.

[0013] In some embodiments, in the XRD spectrum of the composite graphite material, the peak positions of the three strongest peaks of LiF are shifted to the left by 0.15° to 0.25° relative to the peak positions of the three strongest peaks in the standard XRD spectrum of LiF, and the peak positions of the three strongest peaks of NaF are shifted to the right by 0.05° to 0.15° relative to the peak positions of the three strongest peaks in the standard XRD spectrum of NaF.

[0014] A method for preparing a composite graphite material comprises the following steps:

[0015] A first mixed system of graphite, a lithium source solution and a sodium source solution is obtained, the first mixed system is mixed with a fluoride solution to obtain a second mixed system, and the second mixed system is heat treated.

[0016] In some embodiments, the molar ratio of the sum of the element lithium and the element sodium in the lithium source and the sodium source to the graphite is (1-5):100.

[0017] In some embodiments, the molar ratio of the lithium source to the sodium source, calculated as elemental lithium and elemental sodium, is (1-4):1.

[0018] In some embodiments, the concentration of the lithium source solution and the sodium source solution are independently 10% to 40%.

[0019] In some embodiments, the method for preparing the first mixed system specifically includes: mixing part of the graphite with a lithium source solution to obtain a first system, mixing the remaining part of the graphite with a sodium source solution to obtain a second system, and mixing the first system and the second system.

[0020] In some embodiments, the time for mixing part of the graphite with the lithium source solution is 2 to 5 hours; the time for mixing the remaining part of the graphite with the sodium source solution is 2 to 5 hours; and the time for mixing the first system and the second system is 1 to 5 hours.

[0021] In some embodiments, the fluoride includes at least one of NH4F and NH4HF2.

[0022] In some embodiments, the molar ratio of the sum of the elemental sodium and the elemental lithium in the lithium source and the sodium source to the elemental fluorine in the fluoride is 1:(1-1.05).

[0023] In some embodiments, the concentration of the fluoride solution is 10% to 40%.

[0024] In some embodiments, the first mixed system and the fluoride solution are mixed for 2 to 5 hours.

[0025] In some embodiments, the heat treatment temperature is 850-1000° C., and the heat treatment time is 3-7 hours.

[0026] In some embodiments, the heat treatment is performed under protective gas conditions.

[0027] In some embodiments, a drying treatment is performed before the heat treatment, the drying treatment temperature is 70 to 90° C., and the drying time is 8 to 14 hours.

[0028] A negative electrode sheet comprises the composite graphite material.

[0029] A battery comprises the negative electrode sheet.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The composite graphite material of the present invention has a plurality of LiF-NaF composite particles arranged on the surface of the graphite core. LiF is the main inorganic salt component of the SEI film, and plays an important role in protecting the electrode interface and the rapid transmission of lithium ions. NaF has a high ionic conductivity and can inhibit the formation of lithium dendrites, which is beneficial to the improvement of rate performance and cycle performance. NaF and LiF constitute NaF-LiF composite particles, which can inhibit the agglomeration of LiF and are beneficial to the synthesis of a uniform and thin SEI film on the graphite surface, thereby improving the rate performance.

[0032] (2) The preparation method of the composite graphite material of the present invention is simple and easy. By combining the various steps, a composite graphite material having a plurality of NaF-LiF composite particles on the graphite surface is obtained, which has high capacity, high initial efficiency, excellent cycle performance and rate performance.

[0033] (3) The battery prepared from the composite graphite material of the present invention has the characteristics of high capacity and high initial efficiency, and has good cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 This is a scanning electron microscope image (SEM) of the composite graphite material in Example 1 of the present invention;

[0036] Figure 2 This is the energy spectrum (EDS) of the composite graphite material in Example 1 of the present invention;

[0037] Figure 3 is the X-ray diffraction pattern (XRD) of the composite graphite material in Example 1 of the present invention;

[0038] Figure 4 This is a scanning electron microscope image of the composite graphite material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0040] According to one aspect of the present invention, the present invention relates to a composite graphite material, comprising a plurality of composite particles, wherein the composite particles include a graphite core and a plurality of NaF-LiF particles disposed on the graphite core.

[0041] The composite graphite material of the present invention has a plurality of LiF-NaF composite particles arranged on the surface of a graphite core. LiF is a main inorganic salt component of a SEI film, and plays an important role in protecting an electrode interface and rapidly transmitting lithium ions. NaF has a relatively high ionic conductivity, and can inhibit the formation of lithium dendrites, which is beneficial to the improvement of rate performance and cycle performance. NaF and LiF form a NaF-LiF composite structure, which can inhibit the agglomeration of LiF, and is beneficial to the synthesis of a uniform and thin SEI film on the graphite surface, thereby improving the rate performance. Compared with a single LiF coating, the coating of independent LiF particles and NaF particles has a more obvious improvement on the rate and cycle of graphite.

[0042] In some embodiments, the NaF-LiF particles of the present invention have a suitable particle size, and the particle size of the NaF-LiF particles is 10 to 100 nm, including but not limited to 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, or any range between the two.

[0043] In some embodiments, the mass content of the element Li in the composite graphite material is 25 to 180 ppm, including but not limited to 25 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 120 ppm, 150 ppm, 180 ppm, etc., or any range between the two. The mass content of the element sodium in the composite graphite material is 65 to 110 ppm, such as 65 ppm, 70 ppm, 80 ppm, 85 ppm, 90 ppm, 100 ppm, 110 ppm, etc., or any range between the two. The composite graphite material of the present invention contains a suitable mass content of Li and Na elements, that is, contains NaF-LiF composite particles of a suitable mass ratio, which can better improve the performance of graphite, so that the obtained composite graphite material has excellent cycle performance and rate performance.

[0044] In some embodiments, in the composite graphite material, the number of NaF-LiF particles with a particle size of 20 to 80 nm accounts for more than 80%, for example 80.5%, 81%, 82%, 85%, 86%, 88%, 90%, 91%, 92%, 93%, 95%, 98%, 99%, 100%, etc., or any range value between the two. In the present invention, the number of NaF-LiF particles with a particle size of 20 to 80 nm accounts for more than 80% within the above-mentioned suitable range, which is more conducive to ensuring the electrochemical properties of the composite graphite material.

[0045] In some embodiments, in the XRD pattern of the composite graphite material, the peak positions of the three strongest peaks of LiF are shifted to the left by 0.15° to 0.25° relative to the peak positions of the three strongest peaks in the standard XRD pattern of LiF (2θ=38.696°, 44.984°, 65.506°), for example, 0.15°, 0.16°, 0.17°, 0.18°, 0.2°, 0.21°, 0.22°, 0.24° or 0.25°, or any range value therebetween. The three peaks of NaF are shifted to the right by 0.05° to 0.15° relative to the three peaks in the standard XRD spectrum of NaF (2θ=39.010°, 56.353°, 70.664°), such as 0.05°, 0.08°, 0.1°, 0.11°, 0.12°, 0.13°, 0.14°, 0.15°, etc., or any range between the two. The left shift of the LIF peak indicates that the incorporation of Na increases the LiF lattice constant. The right shift of the NaF peak indicates that the incorporation of F may reduce the lattice parameter of NaF; the above changes indicate that the LiF and NaF in the composite graphite material of the present invention are not simply physically mixed, but form NaF-LiF particles.

[0046] According to another aspect of the present invention, the present invention also relates to a method for preparing a composite graphite material, comprising the following steps:

[0047] A first mixed system of graphite, a lithium source solution and a sodium source solution is obtained, the first mixed system is mixed with a fluoride solution to obtain a second mixed system, and the second mixed system is heat treated.

[0048] The preparation method of the composite graphite material of the present invention is simple and easy. The first mixed system is mixed with a fluoride solution. The fluoride solution reacts with a lithium source and a sodium source to generate ammonium hypochlorite. The reaction is not violent, and the material is easily decomposed by heat and is not likely to remain. By combining the steps, a composite graphite material having a plurality of NaF-LiF composite particles on the surface of the graphite is obtained, and the composite graphite material has excellent cycle performance and rate performance.

[0049] In some embodiments, the graphite raw material used in the present invention includes artificial graphite, DV50 = 9 to 9.8 μm, graphitization degree = 93% to 93.6%, and tap density of 1 to 1.05 g / cm 3 , powder pressure is 1.8~2.0g / cm 3 .

[0050] In some embodiments, the molar ratio of the sum of the elemental lithium and the elemental sodium in the lithium source and the sodium source to the graphite is (1-5):100, that is, (Li+Na):graphite=(1-5):100, for example, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, etc., or any range value between the two. The present invention adopts the above-mentioned suitable molar ratio to ensure the proportion of the final NaF-LiF composite particles in the composite graphite material. In some embodiments, the molar ratio of the lithium source and the sodium source, calculated as elemental lithium and elemental sodium, is (1-4):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc., or any range value between the two. The lithium source and the sodium source adopt a suitable molar ratio to ensure the suitable mass content of Na and Li in the final composite graphite material.

[0051] In some embodiments, the lithium source includes at least one of LiOH and LiClO. The sodium source includes at least one of NaClO and NaOH.

[0052] In some embodiments, the concentration of the lithium source solution and the sodium source solution is independently 10% to 40%, that is, the mass content of the lithium source in the lithium source solution is 10% to 40%, and the mass content of the sodium source in the sodium source solution is 10% to 40%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc., or any range between the two. The present invention uses lithium source solution and sodium source solution of appropriate concentrations to be more conducive to the dispersion effect of the graphite raw material, while ensuring the subsequent reaction effect with fluoride (such as NH4F), and ensuring the electrochemical properties of the final composite graphite material.

[0053] In some embodiments, the preparation method of the first mixed system specifically includes: mixing part of the graphite with a lithium source solution to obtain a first system, mixing the remaining part of the graphite with a sodium source solution to obtain a second system, and mixing the first system and the second system. The present invention adopts the above method to prepare the first mixed system, which can better ensure the dispersion effect of graphite and ensure that the subsequent reaction with NH4F is better, so as to form a plurality of NaF-LiF composite particles on the surface of the graphite core, thereby improving the electrochemical properties of the graphite.

[0054] In some embodiments, the time for mixing part of the graphite with the lithium source solution is 2 to 5 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., or any range between the two. In some embodiments, the time for mixing the remaining part of the graphite with the sodium source solution is 2 to 5 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., or any range between the two. In some embodiments, the time for mixing the first system and the second system is 1 to 5 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., or any range between the two. Part of the graphite and the lithium source solution adopts a suitable mixing time, the remaining part of the graphite and the sodium source solution adopts a suitable mixing time, and the first system and the second system adopt a suitable mixing time, which is more conducive to uniform dispersion of materials and ensures the subsequent reaction effect.

[0055] In some embodiments, the fluoride includes NH4F (ammonium fluoride) and / or NH4HF2 (ammonium bifluoride). In some embodiments, the concentration of the fluoride solution (i.e., the mass content of the fluoride) is 10% to 40%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc., or any range between the two.

[0056] In some embodiments, the molar ratio of the sum of the sodium and lithium elements in the lithium source and the sodium source to the fluorine element in the fluoride is 1:(1-1.05), for example, 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.05, etc. The sum of the sodium and lithium elements in the lithium source and the sodium source of the present invention and the fluorine element in the fluoride adopt a suitable molar ratio, which is more conducive to ensuring the improvement effect of the obtained NaF-LiF particles on the rate performance and cycle performance of the composite graphite material.

[0057] In some embodiments, the first mixed system is mixed with the fluoride solution for 2 to 5 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours. The first mixed system of the present invention and the fluoride solution adopt an appropriate mixing time, which is more conducive to the reaction of ammonium fluoride with the lithium source and the sodium source, thereby ensuring that suitable NaF-LiF composite particles are obtained later.

[0058] In some embodiments, the temperature of the heat treatment is 850-1000°C, such as 850°C, 860°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, etc., or any range between the two. The time of the heat treatment is 3-7h, such as 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 7h, etc., or any range between the two. The heat treatment is carried out under protective gas conditions, such as nitrogen, inert gas (argon, helium).

[0059] In some embodiments, drying treatment is performed before heat treatment, and the temperature of drying treatment is 70-90°C, such as 70°C, 75°C, 80°C, 85°C or 90°C, or any range between the two. The drying time is 8-14h, such as 8h, 8.5h, 9h, 9.5h, 10h, 11h, 12h, 13h, 14h, or any range between the two. The drying treatment is carried out under appropriate conditions to remove moisture.

[0060] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the above-mentioned composite graphite material.

[0061] The negative electrode sheet comprises a negative electrode current collector and a negative electrode layer arranged on at least one side surface of the negative electrode current collector, wherein the negative electrode layer comprises the composite graphite material, a conductive agent and a binder.

[0062] According to another aspect of the present invention, the present invention also relates to a battery comprising the above-mentioned negative electrode sheet.

[0063] The battery of the present invention comprises the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte. The battery of the present invention has high capacity, high initial efficiency, excellent cycle performance and rate performance.

[0064] The following is further explained in conjunction with specific embodiments and comparative examples.

[0065] Example 1

[0066] A method for preparing a composite graphite material comprises the following steps:

[0067] (1) Take a certain amount of LiOH and NaOH and dissolve them in water to obtain lithium hydroxide solution (concentration 10%) and sodium hydroxide solution (concentration 10%).

[0068] (2) A certain mass of graphite raw material is divided into two equal parts, and the parts are dispersed in lithium hydroxide solution and sodium hydroxide solution respectively, with Li:Na=1:1 (molar ratio), graphite:(Li+Na)=100:1 (molar ratio), and stirred and mixed for 2 hours to form a first system and a second system; the graphite raw material is artificial graphite, with DV50=9.4 μm, degree of graphitization=93.5%, and tap density of 1.04 g / cm 3 , powder pressure is 1.89g / cm 3 .

[0069] (3) The first system and the second system are mixed for 1 hour to obtain a first mixed system.

[0070] (4) Dissolve NH4F in water to obtain an ammonium fluoride solution with a concentration of 30%; the molar ratio of the lithium hydroxide and the sum of the elements Li and Na in the lithium hydroxide to the element F in NH4F is: (Li+Na):F=1:1, and slowly add it to the first mixed system in step (3) and mix for 5 hours.

[0071] (5) The first mixed system was dried at 80° C. for 12 h, sintered in an Ar atmosphere at a heating rate of 5° C. / min, 850° C., and a holding time of 3 h, and then cooled naturally to obtain a composite graphite material.

[0072] Example 2

[0073] A method for preparing a composite graphite material comprises the following steps:

[0074] (1) Take a certain amount of LiClO and NaClO and dissolve them in water to obtain lithium hypochlorite solution (concentration 40%) and sodium hypochlorite solution (concentration 40%).

[0075] (2) A certain mass of graphite raw material is divided into two equal parts, and dispersed in lithium hypochlorite solution and sodium hypochlorite solution respectively, Li:Na = 2:1 (molar ratio), graphite: (Li + Na) = 100:5 (molar ratio), and stirred and mixed for 3 hours to form the first system and the second system. The graphite raw material is artificial graphite, DV50 = 9.4 μm, graphitization degree = 93.5%, and tap density is 1.04 g / cm3 , powder pressure is 1.89g / cm 3 .

[0076] (3) The first system and the second system formed above were mixed for 5 hours to obtain a first mixed system.

[0077] (4) NH4F is dissolved in water to obtain a 10% ammonium fluoride solution, the molar ratio of the sum of the elements Li and Na in lithium hypochlorite and sodium hypochlorite to the element F in NH4F is: (Li+Na):F=1:1, and the solution is slowly added to the first mixed system in step (3) and mixed for 5 hours.

[0078] (5) The first mixed system was dried at 80° C. for 12 h, sintered in an Ar atmosphere at a heating rate of 2° C. / min, 900° C., and a holding time of 5 h, and then naturally cooled to obtain a composite graphite material.

[0079] Example 3

[0080] A method for preparing a composite graphite material comprises the following steps:

[0081] (1) Take a certain amount of LiClO and NaClO and dissolve them in water to obtain lithium hypochlorite solution (concentration 20%) and sodium hypochlorite solution (concentration 20%).

[0082] (2) A certain mass of graphite raw material is divided into two equal parts, and the parts are dispersed in lithium hypochlorite solution and sodium hypochlorite solution respectively, with Li:Na=2:1 (molar ratio), graphite: (Li+Na)=100:2 (molar ratio), and stirred for 5 hours to obtain the first system and the second system. The graphite raw material is artificial graphite, with DV50=9.4μm, degree of graphitization=93.5%, and tap density of 1.04g / cm 3 , powder pressure is 1.89g / cm 3 .

[0083] (3) The first system and the second system are mixed for 2 hours to obtain a first mixed system.

[0084] (4) NH4HF2 is dissolved in water to obtain a 30% ammonium fluoride solution, the molar ratio of the sum of the elements Li and Na in lithium hypochlorite and sodium hypochlorite to the element F in NH4HF2 is: (Li+Na):F=1:1.05, and the solution is slowly added to the first mixed system in step (3) and mixed for 5 hours.

[0085] (5) The first mixed system was dried at 80° C. for 12 h, sintered in an Ar atmosphere at a heating rate of 5° C. / min, 870° C., and a holding time of 5 h, and naturally cooled to obtain a composite graphite material.

[0086] Example 4

[0087] A method for preparing a composite graphite material comprises the following steps:

[0088] (1) Take a certain amount of LiClO and NaClO and dissolve them in water to obtain lithium hypochlorite solution (concentration 20%) and sodium hypochlorite solution (concentration 20%).

[0089] (2) A certain mass of graphite raw material is divided into two equal parts, and the parts are dispersed in lithium hypochlorite solution and sodium hypochlorite solution respectively, with Li:Na=4:1 (molar ratio), graphite:(Li+Na)=100:2 (molar ratio), and stirred for 3 hours to obtain the first system and the second system respectively. The graphite raw material is artificial graphite, with DV50=9.4μm, graphitization degree=93.5%, and tap density of 1.04g / cm 3 , powder pressure is 1.89g / cm 3 .

[0090] (3) The first system and the second system are mixed for 3 hours to obtain a first mixed system.

[0091] (4) NH4F is dissolved in water to obtain a 40% ammonium fluoride solution, the molar ratio of the sum of the elements Li and Na in lithium hypochlorite and sodium hypochlorite to the element F in NH4F is: (Li+Na):F=1:1, and is slowly added to the first mixed system in step (3) and mixed for 3 hours.

[0092] (5) The first mixed system was dried at 80°C for 12 hours, sintered in an Ar atmosphere at a heating rate of 5°C / min, 1000°C, holding time of 3 hours, and naturally cooled.

[0093] Comparative Example 1

[0094] A method for preparing a composite graphite material comprises the following steps:

[0095] (1) Take a certain amount of LiClO and dissolve it in water to obtain a lithium hypochlorite solution (concentration 20%).

[0096] (2) A certain amount of graphite raw material is dispersed in lithium hypochlorite solution, graphite: Li = 100: 2 (molar ratio), and stirred for 5 hours. The graphite raw material is artificial graphite, DV50 = 9.4 μm, graphitization degree = 93.5%, and tap density is 1.04 g / cm 3 , powder pressure is 1.89g / cm 3 .

[0097] (3) Dissolve NH4F in water to obtain a 30% ammonium fluoride solution, in which the molar ratio of the element Li in lithium hypochlorite to the element F in NH4F is 1:1, and slowly add the solution in step (2) and mix for 5 hours.

[0098] (4) The mixed solution was dried at 80°C for 12 hours, sintered in an Ar atmosphere at a heating rate of 5°C / min, 870°C, and a holding time of 5 hours, and then naturally cooled to obtain a composite graphite material.

[0099] Comparative Example 2

[0100] A method for preparing a composite graphite material comprises the following steps:

[0101] (1) Take a certain amount of lithium fluoride and dissolve it in water to obtain a lithium fluoride aqueous solution.

[0102] (2) Sodium fluoride is added into the lithium fluoride aqueous solution to dissolve it and obtain a mixed solution.

[0103] (3) Disperse the graphite raw material in the mixed solution, Li:Na = 2:1 (molar ratio), graphite: (Li + Na) = 100:2 (molar ratio), stir and mix for 5 hours to obtain a mixed solution. The graphite raw material is artificial graphite, DV50 = 9.4 μm, graphitization degree = 93.5%, and tap density is 1.04 g / cm 3 , powder pressure is 1.89g / cm 3 .

[0104] (4) Drying the mixed solution to obtain graphite with LiF and NaF on the surface.

[0105] Experimental example

[0106] 1. Morphology detection, elemental analysis and X-ray diffraction detection of composite graphite materials The surface morphology of the composite graphite materials in each embodiment and comparative example was tested using a scanning electron microscope (Thermo Fisher Scientific), the element content was analyzed using PerkinElmer (ICP), and the phase analysis of the samples was performed using X-ray diffraction detection (Malvern PANalytical).

[0107] Statistical method for particle size of LiF-NaF particles on the graphite surface of composite graphite materials: three samples are taken for each material, and three 5μm×5μm areas are randomly selected for each sample. The particle size of LiF-NaF particles in the area is counted, and the percentage of LiF-NaF particles with a size of 20-80nm is counted. The results of the three areas are averaged, and finally the three results of each material are averaged to obtain the final result, which is the percentage of small LiF-NaF particles.

[0108] The scanning electron microscope image of the composite graphite material in Example 1 is as follows Figure 1 As shown in FIG. 1 , it can be seen that the LiF-NaF particles are evenly distributed on the surface of the graphite. Figure 4As shown, it can be seen that LiF particles without the addition of NaF tend to grow larger, are unevenly dispersed, and are prone to accumulation.

[0109] The EDS image of the composite graphite material in Example 1 is as follows: Figure 2 As shown, element C, element Na and F in the composite graphite material can be detected, and the F and Na elements are distributed on the graphite surface.

[0110] The XRD pattern of the composite graphite material in Example 1 is as follows: Figure 3 As shown, the characteristic peaks of NaF and LiF were detected, indicating that the two exist in graphite. The peak positions of the three strongest peaks of LiF (2θ=38.696°, 44.984°, 65.506°) are shifted to the left by 0.21°, and the peak positions of the three strongest peaks of NaF (2θ=39.010°, 56.353°, 70.664°) are shifted to the right by 0.15°, indicating that the formed crystal structure is distorted.

[0111] The contents of Li and Na and the percentage of small LiF-NaF particles in the composite graphite materials of various embodiments and comparative examples are shown in Table 1.

[0112] Table 1 Content of Li and Na elements and proportion of LiF-NaF small particles in composite graphite materials

[0113]

[0114] 2. Battery electrochemical performance test

[0115] The composite graphite materials in each embodiment and comparative example were prepared into 2032 button-type half-cells, and their electrochemical properties were tested using a blue electric test system. The button-type half-cell manufacturing process is as follows:

[0116] Graphite raw materials, composite graphite materials obtained in the embodiments and comparative examples, conductive carbon, and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 92:3:5, and then an appropriate amount of N-methylpyrrolidone (NMP) was added to stir into a uniform slurry. After mixing evenly, it was applied on the copper foil current collector, and then dried, rolled, and sliced. The button-type half-cell was assembled in a glove box filled with argon, with a metal lithium sheet as the counter electrode, a 1 mol / L LiPF6 solution as the electrolyte, a 1:1 volume ratio of EC and DMC as the solvent, and a polypropylene composite microporous membrane as the diaphragm. The capacity first effect and rate tests were carried out on a battery tester, the voltage range of charge and discharge was 0.001 to 2V, and the rate performance was tested at 3C and cycle.

[0117] The electrochemical performance test results of the graphite raw materials, the batteries obtained in various embodiments and comparative examples are shown in Table 2.

[0118] Table 2 Electrochemical performance test results of the battery

[0119]

[0120] From Table 1, Figures 1 to 3 It can be seen that the surface of the composite graphite material of the present invention is coated with LiF-NaF particles, and the number of LiF-NaF particles of 20-80 nm accounts for more than 80%, the mass content of Li is 25-180 ppm, and the mass content of Na is 65-110 ppm.

[0121] Compared with the graphite raw material, Example 1 improves the first coulombic efficiency, 3C capacity and capacity retention rate after 300 cycles, and has no significant effect on the capacity. Compared with Example 3, the mass content of Li and Na is less, and the modification effect is not as good as that of Example 3.

[0122] Compared with the raw material, Example 2 improves the initial coulombic efficiency, 3C capacity and capacity retention rate after 300 cycles. Compared with Example 3, the mass content of Li and Na increases, and the capacity decreases.

[0123] Example 4 has more Li and a higher eutectic point, and the coated Na-F particles are larger, so the improvement effect is slightly worse than that of Example 3.

[0124] Compared with Example 3, Comparative Example 1 only coats LiF on the graphite surface, while Example 3 coats LiF-NaF composite particles on the graphite surface. The addition of NaF makes the coating agent evenly distributed on the graphite surface. From the data in Table 2, it can be seen that the LiF-NaF composite particles can improve the cycle performance and rate performance.

[0125] Compared with Example 3, in Comparative Example 2, independent LiF particles and NaF particles are coated on the graphite surface, and in Example 3, LiF-NaF composite particles are coated on the graphite surface. The rate performance and cycle performance of the battery obtained by the graphite surface coated with LiF particles and NaF particles respectively are not as good as the rate performance and cycle performance of the battery obtained by the composite graphite material of Example 3.

[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite graphite material, characterized in that: The invention comprises a plurality of composite particles, wherein the composite particles comprise a graphite core and a plurality of NaF-LiF particles arranged on the graphite core.

2. The composite graphite material according to claim 1, characterized in that: The particle size of the NaF-LiF particles is 10 to 100 nm; And / or, the mass content of element Li in the composite graphite material is 25 to 180 ppm, and the mass content of element sodium is 65 to 110 ppm.

3. The composite graphite material according to claim 2, characterized in that: In the composite graphite material, the number of NaF-LiF particles with a particle size of 20 to 80 nm accounts for more than 80%.

4. The composite graphite material according to claim 1, characterized in that: In the XRD spectrum of the composite graphite material, the peak positions of the three strongest peaks of LiF are shifted to the left by 0.15° to 0.25° relative to the peak positions of the three strongest peaks in the standard XRD spectrum of LiF, and the peak positions of the three strongest peaks of NaF are shifted to the right by 0.05° to 0.15° relative to the peak positions of the three strongest peaks in the standard XRD spectrum of NaF.

5. A method for preparing a composite graphite material, characterized in that: The following steps are involved: A first mixed system of graphite, a lithium source solution and a sodium source solution is obtained, the first mixed system is mixed with a fluoride solution to obtain a second mixed system, and the second mixed system is heat treated.

6. The method for preparing the composite graphite material according to claim 5, characterized in that: Contains at least one of the following features (1) to (4): (1) The molar ratio of the sum of the element lithium and the element sodium in the lithium source and the sodium source to the graphite is (1-5):100; (2) the molar ratio of the lithium source to the sodium source, calculated as elemental lithium and elemental sodium, is (1-4):1; (3) The concentrations of the lithium source solution and the sodium source solution are independently 10% to 40%; (4) The preparation method of the first mixed system specifically comprises: mixing part of the graphite with a lithium source solution to obtain a first system, mixing the remaining part of the graphite with a sodium source solution to obtain a second system, and mixing the first system and the second system.

7. The method for preparing a composite graphite material according to claim 6, characterized in that: The time for mixing part of the graphite with the lithium source solution is 2 to 5 hours; The time for mixing the remaining graphite with the sodium source solution is 2 to 5 hours; The time for mixing the first system and the second system is 1 to 5 hours.

8. The method for preparing a composite graphite material according to claim 6, characterized in that: The invention comprises at least one of the following features (1) to (7): (1) The fluoride comprises at least one of NH4F and NH4HF2; (2) The molar ratio of the sum of the elemental sodium and the elemental lithium in the lithium source and the sodium source to the elemental fluorine in the fluoride is 1:(1-1.05); (3) The concentration of the fluoride solution is 10% to 40%; (4) The first mixed system and the fluoride solution are mixed for 2 to 5 hours; (5) The temperature of the heat treatment is 850 to 1000° C., and the time of the heat treatment is 3 to 7 hours; (6) The heat treatment is carried out under protective gas conditions; (7) A drying treatment is performed before the heat treatment, the drying temperature is 70 to 90° C., and the drying time is 8 to 14 hours.

9. A negative electrode sheet, characterized in that: A composite graphite material comprising any one of claims 1 to 4.

10. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 9.